Die archäologischen Untersuchungen 2016–2021 in Ascoli Satriano/Giarnera Piccola (Prov. Foggia/Apulien) - Heitz, Christian; Laimer, Manuele; Norman, Camilla; Riehle, Kai; Schuchter, Kathrin; Klee, Marlies; Mommsen, Hans (Römische Mitteilungen, 2022)
Recent archaeological investigations at Ascoli Satriano have shed new light on the pre-Roman occupation of northern Apulia (ancient Daunia). The findings document a long-term and locally consistent attachment to the core site of Giarnera Piccola from the 8th to the late 4th century BCE. A close relationship is discerned, both in time and space, of architectural structures and burials. The new local discoveries testify to the existence of this situation from the earliest hut structures onwards and show its persistence until the place’s abandonment. While the detection of new fragments of two Daunian stelae in a shaft/well points to early burial activities, the character of the entangled relationship still has to be scrutinized. Archaeometric and scientific analyses furthermore attest to activities in agriculture and in pottery production.